The transmission of non-banking liquidity shocks to the banking sector - Miguel Sarmiento (Latin American Journal of Central Banking (LAJCB), 2025)
The increasing interdependence between non-banking financial institutions (NBFIs) and the banking sector conditions the provision of liquidity in the financial markets. This paper evaluates how the market stress associated to the bankruptcy of one of the most interconnected NBFIs in an emerging market economy affected the availability and pricing of unsecured interbank funding. The results indicate that the market stress conducted to a reallocation of money market mutual funds (MMMFs) deposits within the banking sector, which affected the banks' liquidity provision in the unsecured interbank market. Banks with an ex-ante high concentration of MMMF deposits significantly increased loan spreads and reduced the supply of unsecured funds in the interbank market. Lending relationships and central bank liquidity contributed to partially alleviate the liquidity shock. Overall, the results suggest that the concentration of uninsured depositors increases the transmission of non-bank liquidity shocks to the banking sector.
Keywords: L14; G12; G2; E58; 330; Banks; Deposits channel; Financial stability; Interbank markets; Lending relationships; MMMF; NBFI